2018
DOI: 10.4110/in.2018.18.e18
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mast Cell Function and Proliferation by mTOR Activator MHY1485

Abstract: Mast cells integrate innate and adaptive immunity and are implicated in pathophysiological conditions, including allergy, asthma, and anaphylaxis. Cross-linking of the high-affinity IgE receptor (FcεRI) initiates diverse signal transduction pathways and induces release of proinflammatory mediators by mast cells. In this study, we demonstrated that hyperactivation of mechanistic target of rapamycin (mTOR) signaling using the mTOR activator MHY1485 suppresses FcεRI-mediated mast cell degranulation and cytokine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…6). That mTOR is important for MC regranulation following MC degranulation is consistent with previous reports showing that activation of mTOR in MCs inhibited IgE mediated MC degranulation and cytokine release as well as their capacity to proliferate 52,53 . Presumably, activating mTOR triggers a metabolic switch in steady state MCs to accommodate regranulation which interferes with both degranulation and MC proliferation activities.…”
Section: Discussionsupporting
confidence: 92%
“…6). That mTOR is important for MC regranulation following MC degranulation is consistent with previous reports showing that activation of mTOR in MCs inhibited IgE mediated MC degranulation and cytokine release as well as their capacity to proliferate 52,53 . Presumably, activating mTOR triggers a metabolic switch in steady state MCs to accommodate regranulation which interferes with both degranulation and MC proliferation activities.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Zhu et al showed that mTOR inhibition suppress eosinophil differentiation in allergic airway inflammation [64], Shin and coll. that reduces eosinophil infiltration and Th2 immune response [65] and Fang et al that IgE induced airway smooth muscle cell (ASMC) remodeling was significantly reduced by inhibition of mTOR [66] while Rakhmanova et al suggested as a therapeutic strategy for mast cell-related diseases the hyperactivation of mTORC1 [67]. The greater role of airway inflammation and remodeling driving severe asthma in women and the regulatory action of estradiol on activation of PI3K/Akt signaling pathway [35], suggests a possible gender specific function of mTOR inhibition.…”
Section: Asthma and Rhinitismentioning
confidence: 99%
“…Recent evidence has additionally demonstrated that the suppression of the malignant phenotype of OS cells by Aurora-B silencing might be achieved via autophagy-mediated activation of the mTOR/ULK1 signaling pathway. Thus, to further investigate the role of the mTOR/ULK1 pathway during Aurora-B silencing-induced autophagy, we investigated the expression of the autophagy-related protein p62 after treatment with MHY-1485, a well-known mTOR activator [ 25 ], or not, in Aurora-B-knockdown or scrambled OS cells. In the Aurora-B-knockdown OS cells, MHY-1485 treatment activated mTOR/ULK1 signaling and increased p62 levels.…”
Section: Resultsmentioning
confidence: 99%